GNB3 C825T polymorphism and elite athletic status: A replication study with two ethnic groups - Ruiz, J. R.; Eynon, N.; Meckel, Y.; Fiuza-Luces, C.; Santiago, C.; Gomez-Gallego, F.; Oliveira, J.; Lucia, A. (International Journal of Sports Medicine, 2011)
We aimed to replicate the original findings by Eynon et al. [4] showing an association between the T allele of the GNB3 C825T polymorphism and elite endurance athletic status, in larger cohorts and in other ethnicities. We compared allelic and genotypic frequencies of the GNB3 C825T polymorphism among non-athletic controls (N=340), elite endurance athletes (N=174), and power athletes (N=134). The population sample included participants from 2 different ethnic/geographic backgrounds (Israel and Spain). We observed no significant differences in genotypic and allelic frequencies between countries or groups (all P>0.1). The odds ratio (OR) of being an endurance athlete if the subject had a T allele was 0.841 (95%CI: 0.638-1.110) compared to the control group and 1.047 (95% CI: 0.751-1.461) compared to the power group. Our findings support the need to corroborate genotype:phenotype associations in the field of sports genetics with the largest possible population samples, including populations of different ethnic backgrounds.